1996
DOI: 10.1007/bf01874847
|View full text |Cite
|
Sign up to set email alerts
|

Can we integrate climatic modelling and assessment?

Abstract: The climatic change "debate" seems to be expanding faster than the available information base. National and international response strategies (mitigation and adaptation) are being discussed in board rooms, governments and the media. Phrases like "the uncertainty in the scenarios" appear to carry meaning but the information seems to be, at best, incomplete and, at worst, totally debased by multiple definitions and usages. "Scenarios" are predictions of possible futures. The "(nn)eertainty" that characterizes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…The range of plausible climate change scenarios is much greater than that determined by uncertainties in climate models alone, and depends to a considerable extent on future global demographic and technological change, land utilisation, and ecological adaptation. Thus, prediction is too ambitious a term for such a tentative and provisional exercise of looking into the future (Henderson-Sellers, 1996). 3 GCM can also stand for "global climate models."…”
Section: Climate Change Scenariosmentioning
confidence: 99%
“…The range of plausible climate change scenarios is much greater than that determined by uncertainties in climate models alone, and depends to a considerable extent on future global demographic and technological change, land utilisation, and ecological adaptation. Thus, prediction is too ambitious a term for such a tentative and provisional exercise of looking into the future (Henderson-Sellers, 1996). 3 GCM can also stand for "global climate models."…”
Section: Climate Change Scenariosmentioning
confidence: 99%
“…The caveats relating to the complexity of the overall biological system make it imperative that the spatial results are interpreted carefully by a biological expert and, ideally, subjected to a number of further sensitivity analyses. As Henderson Sellers commented regarding potential scenarios of climate change, these risk assessments should be seen as 'sketching images of the future' and providing 'vague contours of the plausible …' (Henderson-Sellers, 1996). Nevertheless, we argue that there is scope for fully spatial phenologies to form a useful role within the wider scientific toolbox that is required for the variety of tasks encompassed within the term pest risk analysis.…”
Section: Strategic Issuesmentioning
confidence: 93%
“…As Henderson Sellers commented regarding potential scenarios of climate change, these risk assessments should be seen as 'sketching images of the future' and providing 'vague contours of the plausible …' (Henderson-Sellers, 1996). As Henderson Sellers commented regarding potential scenarios of climate change, these risk assessments should be seen as 'sketching images of the future' and providing 'vague contours of the plausible …' (Henderson-Sellers, 1996).…”
Section: Strategic Issuesmentioning
confidence: 99%
“…Before going into the EFIEA's planned activities in section 3, the next section briefly reviews the state-of-theart in integrated environmental assessment, justifying the need for a more structured approach to IEA. Other reviews and assessments can be found in Bailey [6], Bailey et al [7], Dowlatabadi [13], Henderson-Sellers [26], Hordijk and Kroeze [31], Morgan and Dowlatabadi [46], Parson [52][53][54], Risbey et al [64], Rotmans [68], Rotmans and Dowlatabadi [70], Rotmans and van Asselt [69], Schneider [72], Weyant [81] and Weyant et al [82]. Section 4 concludes by describing the possible benefits of the EFIEA.…”
Section: Introductionmentioning
confidence: 99%